Metabolic imbalances, hoof injuries, and metabolic profile of high-producing Holstein × Gir cowsshowing lameness - Cucunubo Santos,Luis G. (2022)
ABSTRACT: This study attempted to determine the associations between metabolic imbalances and lameness or hoof injuries in high-producing Holstein × Gir cows, and to determine whether the metabolic profile affects the occurrence of lameness. Eighty cows were followed from -60 to 60 days relative to calving and hoof injuries were reported on days -60, 7 and 60. Locomotion score (LS), body condition score (BCS), the concentrations of non-esterified fatty acids, β-hydroxybutyrate, glucose, cholesterol, albumin, total protein, blood urea nitrogen (BUN), calcium, phosphorus, and magnesium, and the activity of aspartate aminotransferase were determined at days -42, -21, -7, 0, 7, 21 and 42. The McNemar and Chi-square tests were used to compare frequencies of lameness and hoof injuries over time and to verify the associations between lameness, BCS, hoof injuries, and metabolic disorders. Two-way repeated measures ANOVA was used considering groups (non-lame × lame cows) and variations of BCS and metabolites over time. Lameness and hoof injuries increased between days -60 (20% and 66.3%) and 60 (44.7% and 98.6%). Excessive postpartum loss of BCS (P=0.017) and subclinical hypocalcemia (P=0.012) were associated with lameness on day 60. In general, the metabolic profile did not differ between lame and non-lame cows but cholesterol, albumin, BUN and magnesium concentrations were higher in non-lame cows. The postpartum decrease in BCS can affect the occurrence of lameness, and the metabolic profile of lame cows shows little difference from that of non-lame cows.